2015
DOI: 10.1016/j.supflu.2015.04.016
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous measurement of fluids density and viscosity using HP/HT capillary devices

Abstract: International audienceAccessing fluids thermophysical properties is crucial in chemical engineering for they are required inmost of process parameter calculations. Nevertheless, these are not always available in the literature. Inthe present paper, we propose a fast and efficient microfluidic approach for simultaneously accessingdensity and viscosity of homogeneous fluids mixtures. In comparison with classical set-ups, microfluidicdevices exhibit higher heat transfer capability and small volumes, resulting in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…Since the flow inside a microfluidic channel is laminar, inertial forces are very small compared to viscous forces, therefore, observing them is challenging in conventional microfluidic systems. However, Pinho et al 79 showed they can simultaneously determine the viscosity and the density of a fluid mixture by measuring the pressure drop between the inlet and the outlet of a flow in a capillary. The only condition for this process to stay in a reasonable range of precision, the pressure drop should not increase too much to significantly change the fluid mixture thermophysical properties.…”
Section: Densitymentioning
confidence: 99%
See 1 more Smart Citation
“…Since the flow inside a microfluidic channel is laminar, inertial forces are very small compared to viscous forces, therefore, observing them is challenging in conventional microfluidic systems. However, Pinho et al 79 showed they can simultaneously determine the viscosity and the density of a fluid mixture by measuring the pressure drop between the inlet and the outlet of a flow in a capillary. The only condition for this process to stay in a reasonable range of precision, the pressure drop should not increase too much to significantly change the fluid mixture thermophysical properties.…”
Section: Densitymentioning
confidence: 99%
“…Table 2 gives a comparison of the different density ranges measured in some of the studies detailed above, depending on their approach. The approach developed by Pinho et al 79 is the only non-MEMS based study, however the mass flow rates of the different compounds of the fluid mixture need to be known. Mass transfer and solubility measurement strategies at micro-scale…”
Section: Densitymentioning
confidence: 99%
“…The most employed solvents are CO 2 and H 2 O; however, when designing the material synthetic path, they could be the combination of two or more fluids, the mixture thus having different properties, which can be clearly seen in the modification of critical pressures and temperatures, specific to defined compositions (Figure 1B). These thermodynamics -essential to design processes -can be obtained through the use of high-pressure cells, although we recently demonstrated much faster microfluidic approaches for investigating these multicomponent systems' thermodynamics under pressure and temperature [29,30]. The solubility of the precursors being dependent on the solvent's density could be controlled by slight changes in the reaction's pressure and temperature, or by the addition of co-solvent(s).…”
Section: What Makes Scfs So Special [3 23-28]?mentioning
confidence: 99%
“…Very recently, high-pressure microfluidic platforms have been developed to investigate the behaviors of CO 2 with a background fluid at high pressure and temperature to simulate the conditions of deep saline formations, which typically have the pressure (P) range of 6 MPa < P < 27 MPa and the temperature (T) range of 26°C < T < 110°C. 27 For example, the investigations using high-pressure microfluidics have focused on the flow patterns of CO 2 displacing fluid, 28,29 the applications of CO 2 in oil recovery processes, 30,31 physical properties (e.g., density and viscosity) at the supercritical state, 32 fast screening of the CO 2 phase state in different solvents, 33,34 and solubility of CO 2 in brine. 35 Nevertheless, microfluidic experimental studies regarding the CO 2 transport rate in water or brine under P-T conditions close to or under reservoir conditions are relatively limited.…”
Section: Introductionmentioning
confidence: 99%